Implementasi Peraturan Daerah Nomor 1 Tahun 2024 Tentang Pelestarian dan Pengelolaan Cagar Budaya di Kota Surabaya - Ahmad Bayu Dwi Rahman; M Kendry Widiyanto; Hasan Ismail (Universitas 17 Agustus 1945 Semarang, 2025)
Surabaya known as the City of Heroes, has various historical buildings scattered in strategic areas, one of which is in Kota Lama Surabaya. The existence of these buildings has been designated as cultural heritage that must be preserved in order to maintain the historical value and identity of the city. However, the implementation of preservation still encounters various obstacles, especially in technical and administrative aspects, as well as the lack of public understanding of the importance of preservation. This research aims to describe the implementation of Surabaya City Regional Regulation Number 1 Year 2024 on the Preservation and Management of Cultural Heritage, with a focus on De Javasche Bank Museum as the object of research. Researchers used descriptive qualitative methods with data collection techniques in the form of interviews, field observations, documentation, and review of policy documents. The implementation theory of Ripley and Franklin was used as an analytical knife that includes three indicators, namely the level of compliance with regulations, the smooth routine of functions and coordination between implementers, and the realization of the desired performance and impact. The results show that the implementation of the local regulation has shown progress at the institutional level through coordination across Regional Apparatus Organizations and the implementation of SOPs by museum managers. However, there are still obstacles such as the lack of optimal human resources experts, weak administrative coordination, and the absence of a special management institution. Positive impacts such as increased visitation and community involvement are starting to be seen, but the overall effectiveness of implementation still requires strengthening in various sectors to ensure the sustainability of inclusive preservation.